PERANCANGAN ALAT PIROLISIS PORTABLE UNTUK PEMBUATAN ASAP CAIR DARI LIMBAH PELEPAH KELAPA SAWIT - Mila Lukmana; Baimy Alexander; Herry Iswahyudi (Universitas Lambung Mangkurat, 2022)
Solid waste from oil palm plantations and industries generally contains high organic matter so that it is environmentally possible. The pyrolysis technique is currently an effective technology in the handling of palm oil waste because in the process a biochar product is produced, immediately liquid which has high heat and can be used in agriculture. Generally, pyrolysis equipment has a large size with a large capacity. In addition, controlled pyrolysis is usually found in pilot-scale or relatively large dimensions for industrial-scale that have been assembled so that they are not easy to carry and move. The purpose of this study is to design a portable pyrolysis equipment that is easy to use and move to handle palm oil solid waste. The stages of the research carried out were the manufacture of a pyrolysis device and the testing stage of the tool. Testing the pyrolysis tool using raw material from palm oil midrib-leaf waste. Tool testing is carried out to determine whether the tool works well, to determine the yield (%) produced and the working capacity of the tool (Kg/Hour). The results of this study are the stages of the process of making a portable pyrolysis tool including making reactors, making condensers, installation processes and automation of tools with control panels, making tool tables, and assembling tools. The test results show the yield of the tool is 39,1% and the working capacity of the tool is 0,24 kg/hour.